2015
DOI: 10.1371/journal.pone.0117251
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography Assessment of the Maxillary Incisive Canal and Foramen: Considerations of Anatomical Variations When Placing Immediate Implants

Abstract: IntroductionThe maxillary incisive canal connects the roof of the oral cavity with the floor of nasal cavity and has the incisive and nasal foramina respectively at its two opposite ends. Its close proximity with the anterior incisors affects one’s ability to place immediate implants in ideal position.ObjectiveTo avoid causing complication, variations in their dimensions were studied.Material and MethodsImages of ninety Mongoloids patients examined with i-CAT Cone Beam Computed Tomography were included. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
74
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 23 publications
13
74
2
3
Order By: Relevance
“…For Al-Amery et al (3) and Kajan et al (7), the labiopalatal (anteroposterior) diameter of the IF was 2.80 ±0.82 and 3.53 ± 1.1 mm respectively.…”
Section: Discussionmentioning
confidence: 90%
“…For Al-Amery et al (3) and Kajan et al (7), the labiopalatal (anteroposterior) diameter of the IF was 2.80 ±0.82 and 3.53 ± 1.1 mm respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Although limited by a small sample, the previously mentioned Lebanese study found that the length of the canal was shorter in females [ 3 , 21 - 23 ]. Additionally, the length of the canal also varies based on the height of the maxillary bone [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Morphological depictions of the direction and course of the canal from sagittal imaging views are described as vertical, vertically curved, slanted straight, or slanted curved [ 22 ]. Regarding the angulation of the canal, Song et al reported the slanting angle of the canal, i.e., the angle taken from a vertical reference point, ranged between -7.4 and 35.3 degrees [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…The oral opening of the NPC, the incisive foramen, is found in this region which maintains close proximity to the roots of the upper central incisors [4] [5]. In view of this anatomical relationship, thorough radiographic analysis is necessary during dental implant planning [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, knowledge of anatomical variations in the size, shape and number of the NPC is important, but studies on this topic are sparse [4] [7] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%